(untitled) (Research, Society and Development, 2021)
Cookies are characterized by high acceptance and allow the use of versatility of ingredients in their formulations. The aim of this study was to prepare cookies with the mixture of beet stalk flour (FTB), oat flakes (FA) and wheat flour (FT) and evaluate their physical, chemical and sensory characteristics. Cookies were developed using the simplex centroid experimental design, with a central point and restriction of the maximum limit of wheat flour by 50%. In the cookies, water activity (Aw), pH, Ho, C * and acceptance of the attributes flavor, texture and overall appearance were determined. The linear model proved to be the most adequate to explain the variation in Aw, pH and all sensory attributes, the quadratic model was able to predict the variations in Ho and C *. FTB had a synergistic effect on Aw and antagonistic on pH, whereas the opposite was observed for FA. The cookies made with FTB were brown in color and with less color purity, while the FA and FT originated golden cookies and with greater color purity. Sensory attributes were negatively affected by the presence of FTB. Therefore, FTB had a marked influence on physical, chemical and sensory parameters. However, it is noteworthy that when FTB was used in up to 17% of the meal base, good results were obtained.